Small proteins: untapped area of potential biological importance - Su, Mingming; Ling, Yunchao; Yu, Jun; Wu, Jiayan; Xiao, Jingfa (Frontiers in Genetics, 2013)
Polypeptides containing ≤ 100 amino acid residues are generally considered to be small proteins. Many studies have shown that some small proteins are involved in important biological processes, including cell signaling, metabolism and growth. Small protein generally has a simple domain and has an advantage to be used as model system to overcome folding speed limits in protein folding simulation and drug design. But small proteins were once thought to be trivial molecules in biological processes compared to large proteins. Because of the constraints of experimental methods and bioinformatics analysis, many genome projects have used a length threshold of 100 amino acid residues to minimize erroneous predictions and small proteins are relatively under-represented in earlier studies. The general protein discovery methods have potential problems to predict and validate small proteins, and very few effective tools and algorithms were developed specially for small proteins identification. In this review, we mainly consider the diverse strategies applied to small proteins prediction and discuss the challenge for differentiate small protein coding genes from artifacts. We also summarize current large-scale discovery of small proteins in species at the genome level. In addition, we present an overview of small proteins with regard to biological significance, structural application and evolution characterization in an effort to gain insight into the significance of small proteins.